PENGARUH MODEL PROJECT BASED LEARNING PADA MATA KULIAH PENDIDIKAN KEWARGANEGARAAN TERHADAP KARAKTER INTEGRASI NASIONAL MAHASISWA TEKNIK INFORMATIKA - Ita Aristia Sa'ida (IICLS (Indonesian Institute for Corporate Learning and Studies), 2022)
To achieve the learning objectives of civic education, strategies and models are needed in learning that can increase student participation and creativity and be able to instil character values in students and national integration of informatics engineering students. To instil character values in students and national integration of informatics engineering students, researchers chose a Project-Based Learning model based on projects / activities as a medium. Through this project-based learning, lecturers are required to be able to shape and build the character of students who love the country and are able to carry out foreign activities. For this reason, the author is interested in conducting research with the theme